IVIG and rituximab for treatment of chronic antibody-mediated rejection: a prospective study in paediatric renal transplantation with a 2-year follow-up - Billing, Heiko; Rieger, Susanne; Süsal, Caner; Waldherr, Rüdiger; Opelz, Gerhard; Wühl, Elke; Tönshoff, Burkhard (Transplant international, 2012)
Chronic antibody-mediated rejection (AMR) is the major cause of late renal allograft loss. There is, however, no established treatment for this condition. We report the results of a prospective pilot study on an antihumoral therapy (AHT) consisting of high-dose intravenous immunoglobulin G (IVIG) and rituximab in 20 paediatric renal transplant recipients. Donor-specific HLA antibodies (HLA DSA) were quantified by Luminex-based bead array technology. Loss of eGFR decreased significantly from 7.6 ml/min/1.73 m² during 6 months prior to AHT to 2.1 ml/min/1.73 m² (P = 0.0013) during 6 months after AHT. Fourteen patients (70%) responded: nine of nine patients (100%) without and five of 11 (45%) with transplant glomerulopathy (P = 0.014). C4d positivity in PTC decreased from 40 ± 18.5% in the index biopsy to 11.6 ± 12.2% (P = 0.002) in the follow-up biopsy. In four of nine biopsies (44%) C4d staining turned negative. During 2 years of follow-up, the median loss of eGFR in each of the four 6-month periods remained significantly lower compared with prior to AHT. Class I DSA declined in response to AHT by 61% (p = 0.044), class II DSA by 63% (p = 0.033) 12 months after intervention. AHT with IVIG and rituximab significantly reduces or stabilizes the progressive loss of transplant function in paediatric patients with chronic AMR over an observation period of 2 years, apparently by lowering circulating DSA and reducing intrarenal complement activation.